Songbook - Galvez, Marisa (University of Chicago Press, 2012)
Today we usually think of a book of poems as composed by a poet, rather than assembled or adapted by a network of poets and readers. But the earliest European vernacular poetries challenge these assumptions. Medieval songbooks remind us how lyric poetry was once communally produced and received-a collaboration of artists, performers, live audiences, and readers stretching across languages and societies. The only comparative study of its kind, Songbook treats what poetry was before the emergence of the modern category
Description based on publisher supplied metadata and other sources
Keywords: Ruiz; Juan; Libro de buen amor; Mittelhochdeutsch; Okzitanisch; Spanisch; Liederbuch; Lyrik; Mittelalter; Buchmalerei